(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article provides an in-depth analysis of the role of strong families and active women in ensuring the prosperity and sustainable development of society. The family is one of the most important social institutions, where values, mutual respect, and moral foundations are shaped and transmitted to future generations. Women play a crucial role both within the family and in the wider community, as their activity significantly contributes to national progress. Today, women are achieving remarkable success in education, healthcare, culture, politics, and the economy. Their initiative, patience, and dedication not only strengthen family stability but also foster overall societal development. Governments are implementing large-scale reforms aimed at supporting women, protecting their rights, and increasing their participation in socio-economic life. Therefore, strong families and active women represent not only the pillars of social stability but also the essential guarantees of prosperity and harmony for the future.